Infusing Qur'anic standards into the IEEE Code of Ethics - Shuriye, Abdi Omar (Islamic Centre for Education, Research and Development, 2009)
IEEE has over the years become one of the most renown and the world's leading professional society for the innovation of engineering technology. With its 365,000 members in over 150 countries, and 311 sections in ten geographic regions worldwide, this association is an authority on areas ranging from biomedical engineering, aerospace, el,ectric power, computers and telecommunications. This part of the work serves as the first attempt to pervade Islamic standards into the IEEE Code of Ethics. As these codes govern a Large number of professionals, studying them from Qur'anic perspective or permeating Islamic values into each code, will certain|y help professionals globally to comprehene{ rhe Qur'anic approach to valuesl c The airn is to popularize the approach of infusing eura'nic values into professional codes and ro enrich the resources on professional ethics from Qur'anic perspective, As this is the first attempr of its kind the author hopes rclay the foundation or rather formulate the future directions of Muslim professionals in research, and practice. The Qur'an accentuates professional awareness and mindfulness in the process of discharging engineering decisions and for development and maintaining of engineering related, industrial and manufacturing works. To this effect the Qur'an denounces all kinds of irresponsibility in designing and construction.